'Nature-inspired' drug–protein complexes as inhibitors of Aβ aggregation. (1st August 2005) - Bose, M.; Gestwicki, J.E.; Devasthali, V.; Crabtree, G.R.; Graef, I.A.
Abstract : Protein–protein interactions are a regulatory mechanism for a number of physiological and pathological cellular processes. Neurodegenerative diseases, such as AD (Alzheimer's disease), are associated with the accelerated production or delayed clearance of protein aggregates. Hence, inhibition of pathologic protein–protein interactions is a very attractive mechanism for drug development. This review focuses on a novel therapeutic strategy to inhibit the de novo formation of protein aggregates. Inspired by strategies used in Nature and optimized over millions of years of evolution, we have created a bifunctional molecule [SLF (synthetic ligand for FK506-binding protein)–CR (Congo Red)] that is able to block Aβ (amyloid β) aggregation by borrowing the surface and steric bulk of a cellular chaperone.